Analysis and Evaluation of the Logistics of Armenia's Transport Routes in Foreign Trade - Mariam Voskanyan; Ani Galstyan (Sustainable Development and Engineering Economics)
The current geopolitical picture of the world has become a serious challenge for many countries. In addition to many different turbulent phenomena, changes in logistics and transport routes between countries can also be observed in the global economy of the current period. Along with the changing roles and the struggle for various geopolitical interests, issues of transport communications and transit opportunities for countries are coming to the fore. The problem of developing transport and logistics routes has become even more urgent for Armenia and requires an immediate solution. The key objective of the study was to assess the possibilities of Armenia's transport logistics in terms of its interaction with both countries and third countries, including from the perspective of expanding re-exports over the past few years. The research methodology is based on the analysis of the impact of transport communications on the economic development and well-being of Armenia. Methods of qualitative and statistical analysis, as well as observation and synthesis are used. The information base includes statistics on cargo transportation and the commodity structure of Armenia's trade with the EAEU and third countries. As a result, it was revealed that the existing transport and logistics system of Armenia is poorly developed and significantly hinders the development of the country's economic potential. The main conclusion of the study was the thesis about the need to develop logistics transport systems in order to have a positive impact on Armenia's economic growth and development in the long term.